Dietary Spirulina platensis to Increase Color Brightness and Growth of Betta Fish, Betta splendens - Alhan Ferdyawan Saputra; Achmad Noerkhaerin Putra; Mas Bayu Syamsunarno (Jurnal Biologi Tropis, 2023)
Betta fish (Betta splendens) are ornamental fish that have a unique color and high economic value. The aim of this research was to evaluate the addition of different doses of S. platensis in feed on color brightness and growth of betta fish. Betta fish (length of 32±4.4 mm) were maintained in containers with a volume of 4 liters at a density of 1 fish/container for 35 days and feeding is done twice a day at satiation. This research consisted of 4 treatments adding different doses of S. platensis in the feed and 5 repetitions, namely: P1: adding S. platensis 0%, P2: adding S. platensis 1%, P3: adding S. platensis 1.5%, and P4: addition of S. platensis 2%. The research results showed that the carotenoids contained in S. platensis are 737.16 ppm/50 g. The addition of S. platensis in feed can improve the color quality of betta fish but does not affect the growth of betta fish. The addition of 1.5% S. platensis in the feed produced the highest values in the parameters of color brightness (9.1 in the 4th week), color diversity (body 62.54%, base of tail 59.52% and tail 61 .22%), and chromatophore cell area (673000 µm2).